Mometasone furoate in the treatment of mild, moderate, or severe persistent allergic rhinitis: a non-inferiority study (PUMA) - Antila,Martti Anton (2016)
ABSTRACT INTRODUCTION: Allergic rhinitis is considered the most prevalent respiratory disease in Brazil and worldwide, with great impact on quality of life, affecting social life, sleep, and also performance at school and at work. OBJECTIVE: To compare the efficacy and safety of two formulations containing mometasone furoate in the treatment of mild, moderate, or severe persistent allergic rhinitis after four weeks of treatment. METHODS: Phase III, randomized, non-inferiority, national, open study comparing mometasone furoate in two presentations (control drug and investigational drug). The primary endpoint was the percentage of patients with reduction of at least 0.55 in nasal index score (NIS) after four weeks of treatment. Secondary outcomes included total nasal index score score after four and 12 weeks of treatment; individual scores for symptoms of nasal obstruction, rhinorrhea, sneezing, and nasal pruritus; as well as score for pruritus, lacrimation, and ocular redness after four and 12 weeks of treatment. The study was registered at clinicaltrials.gov with the reference number NCT01372865. RESULTS: The efficacy primary analysis demonstrated non-inferiority of the investigational drug in relation to the control drug, since the upper limit of the confidence interval (CI) of 95% for the difference between the success rates after four weeks of treatment (12.6%) was below the non-inferiority margin provided during the determination of the sample size (13.7%). Adverse events were infrequent and with mild intensity in most cases. CONCLUSION: The efficacy and safety of investigational drug in the treatment of persistent allergic rhinitis were similar to the reference product, demonstrating its non-inferiority.